Efficacy and safety of short-term spinal cord stimulation and pulsed radiofrequency in the treatment of postherpetic neuralgia: a meta-analysis - Liu, Zehao; Weng, Yan; Liu, Funing; Jiang, Dezhou; Wu, Chunmei; Chen, Yong; Duan, Xiaoxia; Zhong, Qing (Frontiers in Neurology, 2025)
ObjectiveThis study aimed to explore the efficacy and safety of short-term Spinal Cord Stimulation (stSCS) and Pulsed Radiofrequency (PRF) in the treatment of postherpetic neuralgia (PHN).MethodsWe searched the PubMed, Cochrane Library, Web of Science, Embase, China Biological Medicine Database (CBM-disk), Chinese National Knowledge Infrastructure (CNKI), Wanfang, and VIP databases for randomized controlled trials (RCTs) from the establishment of the database to August 1, 2024. Review Manager 5.4 and Stata 18.0 were used for the meta-analysis.ResultsIn total, eight randomized controlled trials comprising 479 patients were included. Meta-analysis showed that compared with PRF, stSCS had better pain relief (p < 0.01), lower Pain Rating Index Affective (PRI-A) score (p < 0.01), lower Pain Rating Index Sensory (PRI-S) score (p = 0.002), better sleep quality (p = 0.02), higher effective rate (p < 0.01), and lower incidence of postoperative complications (p = 0.007). However, complete remission rate (p = 0.24) after the two treatment methods were similar between the two groups. Moreover, stSCS treatment is more expensive.ConclusionIn general, stSCS is a more effective and safe method for the treatment of PHN, but its high cost is an unavoidable problem. Each method has advantages and disadvantages that should be considered comprehensively in clinical practice.Systematic review registration:https://www.crd.york.ac.uk/PROSPERO/, identifier CRD42024576536.